Simplifying plant gene silencing and genome editing logistics by a one-Agrobacterium system for simultaneous delivery of multipartite virus vectors - Aragonés, Verónica; Aliaga, Flavio; Pasin, Fabio; Daròs, José Antonio (Wiley, 2022)
Viral vectors provide a quick and effective way to express exogenous sequences in eukaryotic cells and to engineer eukaryotic genomes through the delivery of CRISPR/Cas components. Here, we present JoinTRV, an improved vector system based on tobacco rattle virus (TRV) that simplifies gene silencing and genome editing logistics. Our system consists of two mini T-DNA vectors from which TRV RNA1 (pLX-TRV1) and an engineered version of TRV RNA2 (pLX-TRV2) are expressed. The two vectors have compatible origins that allow their cotransformation and maintenance into a single Agrobacterium cell, as well as their simultaneous delivery to plants by a one-Agrobacterium/two-vector approach. The JoinTRV vectors are substantially smaller than those of any known TRV vector system, and pLX-TRV2 can be easily customized to express desired sequences by one-step digestion-ligation and homology-based cloning. The system was successfully used in Nicotiana benthamiana for launching TRV infection, for recombinant protein production, as well as for robust virus-induced gene silencing (VIGS) of endogenous transcripts using bacterial suspensions at low optical densities. JoinTRV-mediated delivery of single-guide RNAs in a Cas9 transgenic host allowed somatic cell editing efficiencies of ≈90%; editing events were heritable and >50% of the progeny seedlings showed mutations at the targeted loci.